Developing Narrative Text Material Integrated on Kurikulum Merdeka at MAN Labuhanbatu - Harahap, Nurhanna; Rusli, Muhammad; Lestari, Rizki; Hasibuan, Khoiria Rahmadani; Pasaribu, Endi Zunaedy (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The purpose of this research is to describe the process of developing narrative text integrated on kurikulum merdeka and to determine whether the product has an impact on English achievement for the tenth grades students at MAN Labuhanbatu. This research are Research and Development (R&D) by using ADDIE model. To gather information, two different kinds of questionnaires were employed and post-test. The first questionnaire was created to collect information for the needs analysis, the second to evaluate materials using professional judgment, and the last to evaluate the efficacy of the product. The created materials were deemed suitable based on the outcomes of the expert judgment. The developed narrative text materials were categorized as "Very Good" with a mean score of 3.95 across all aspects. The developed narrative text material has an impact on English achievement, 88.88% were obtained based on post-test and categorize as “Good”. Based on the results, it shows that the developed narrative text material is categorized as very good and has an impact on students' English learning achievement.